Teaching Graphic Novels in the English Classroom Pedagogical Possibilities of Multimodal Literacy Engagement (Springer International Publishing, 2018)
This collection highlights the diverse ways comics and graphic novels are used in English and literature classrooms, whether to develop critical thinking or writing skills, paired with a more traditional text, or as literature in their own right. From fictional stories to non-fiction works such as biography/memoir, history, or critical textbooks, graphic narratives provide students a new way to look at the course material and the world around them. Graphic novels have been widely and successfully incorporated into composition and creative writing classes, introductory literature surveys, and upper-level literature seminars, and present unique opportunities for engaging students' multiple literacies and critical thinking skills, as well as providing a way to connect to the terminology and theoretical framework of the larger disciplines of rhetoric, writing, and literature.